2017
DOI: 10.1177/0961000617726126
|View full text |Cite
|
Sign up to set email alerts
|

How do public librarians constitute information literacy?

Abstract: The public library has historically been entrusted with the design and delivery of services and programmes aimed at supporting the information literacy needs of the community-atlarge. However, despite that central role little research has been devoted to understanding the ways in which public librarians, the conduit between the programme and the public, constitute the very concept (information literacy) they are delivering. This study has sought to redress that inequity by way of a phenomenographic study into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Another point of common ground/fight of Marton phenomenography with phenomenology is with the idea human differences/experiences of students needed to make not only the classroom fairer and more inclusive but the world in general. Nevertheless, Bruce (1994Bruce ( , 1997Bruce ( , 1999Demasson et al 2017) developed a variant of phenomenography arguably much wider than Marton education-focused phenomenography portrayed above. Phenomenography is understood as a study of differences in how people experience the world around them.…”
Section: Phenomenology and Research Methodsmentioning
confidence: 99%
“…Another point of common ground/fight of Marton phenomenography with phenomenology is with the idea human differences/experiences of students needed to make not only the classroom fairer and more inclusive but the world in general. Nevertheless, Bruce (1994Bruce ( , 1997Bruce ( , 1999Demasson et al 2017) developed a variant of phenomenography arguably much wider than Marton education-focused phenomenography portrayed above. Phenomenography is understood as a study of differences in how people experience the world around them.…”
Section: Phenomenology and Research Methodsmentioning
confidence: 99%
“…Another study of Demasson, Partridge and Bruce (2017) revealed that the respondents constituted information literacy in four ways, as: intellectual process, technical skills, navigating the social world and gaining the desired result. The findings and the attending study will help to provide a new evidence base that assists in the design and delivery of activities supporting future information literacy endeavors in the nation's public libraries [8] . The librarian's multiple roles as an expert searcher, organizer, and analyzer form an integral part of the Cochrane Collaboration's criteria for conducting systematic reviews [Harris (2005)].…”
Section: Introductionmentioning
confidence: 91%
“…The above case studies demonstrate that public libraries are in the right position to offer information literacy skills to the public and the fact that public librarians are capable of doing so (Demasson et al, 2019). Information literacy sessions such as reference sessions, search skills for the web, knowledge of information sources, OPAC and databases are very important to the public.…”
Section: Review Of Related Literaturementioning
confidence: 98%